2016
DOI: 10.1590/2317-1782/20162015002
|View full text |Cite
|
Sign up to set email alerts
|

Postura e equilíbrio corporal de escolares de oito a doze anos com e sem respiração oral

Abstract: RESUMO Objetivo Avaliar a postura e o equilíbrio corporal de escolares com e sem respiração oral e, ainda, verificar se existe correlação entre os valores obtidos na avaliação da postura corporal e na análise dos sistemas sensoriais. Método A pesquisa foi realizada com escolares de 8 a 12 anos. A amostra foi subdividida em grupo estudo (escolares com respiração oral) e grupo controle (escolares sem respiração oral). A divisão dos grupos foi determinada com base em critérios pré-estabelecidos pesquisados na ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
3
0
6
Order By: Relevance
“…In 2013, Novo et al [ 57 ] reported that when Class II or Class III was present, children adopted positions that allowed them to compensate for their mandibular retraction or protrusion, respectively, by seeking a postural balance. Many studies have examined the relationship between the stomatognathic apparatus and body posture, [ 9 ] but few have been conducted to consider possible relations with more distant segments, taking into account variables providing suitable validity and reliability for both segments; among these, Rothbart [ 58 ] examined the relation between pronated feet, the innominate bones and vertical facial dimensions, and observed a positive relation between relatively pronated feet, anterior rotation of the hip, and a shortening of the vertical facial dimension. Valentino, [ 26 ] in a study based on electromyography, detected a correlation between the interdental occlusal plane and the muscles of the plantar arches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Novo et al [ 57 ] reported that when Class II or Class III was present, children adopted positions that allowed them to compensate for their mandibular retraction or protrusion, respectively, by seeking a postural balance. Many studies have examined the relationship between the stomatognathic apparatus and body posture, [ 9 ] but few have been conducted to consider possible relations with more distant segments, taking into account variables providing suitable validity and reliability for both segments; among these, Rothbart [ 58 ] examined the relation between pronated feet, the innominate bones and vertical facial dimensions, and observed a positive relation between relatively pronated feet, anterior rotation of the hip, and a shortening of the vertical facial dimension. Valentino, [ 26 ] in a study based on electromyography, detected a correlation between the interdental occlusal plane and the muscles of the plantar arches.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, body posture is a static moment with very limited periods of oscillation, whereas body balance is a dynamic moment that can be maintained even if a major or minor oscillation of the body occurs. [ 9 ] Postural attitude is defined as the general posture of the joints in the body at a given time, whereas static postural alignment is the relative positioning of several body segments and joints. Postural alterations may affect various body systems, including the stomatognathic system, [ 10 ] and posture-related pathologies are known to affect different parts of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Em um alinhamento postural ideal, espera-se que os músculos, articulações e suas estruturas encontrem-se em estado de equilíbrio dinâmico, gerando uma quantidade mínima de esforço e sobrecarga (Żuk, et al, 2019;Schmit, et al, 2016;Cramer, et al, 2018). A avaliação postural é um método amplamente utilizado na fisioterapia para compreensão do alinhamento dos segmentos corporais, cuja finalidade é manter o corpo equilibrado, ou seja, projetar o centro de gravidade na base de sustentação, administrando assim, a força gravitacional (Poça, 2019;Santos & Munguba, 2018;Roggia, 2016). De maneira geral, estudos relatam diversos métodos de análise biomecânica da postura em posição estática, entre estes, a fotogrametria digital (Malko, et al, 2020;Ferreira, et al, 2016).…”
Section: Introductionunclassified
“…O Sistema Nervoso Central (SNC) engloba as informações do sistema vestibular, visual e somatossensorial objetivando harmonizar os movimentos da cabeça e do corpo associados à gravidade, à superfície e ao meio ambiente para proporcionar a sustentação da postura ereta, auxílio na noção espacial e desenvolvimento do desempenho motor e locomoção (TOMAZ et al, 2014). Os reflexos e o SNC são responsáveis pela organização do sistema de controle postural (MASSION, 1998), que é composto pelo equilíbrio e pela postura corporal, que são dois mecanismos distintos (ROGGIA et al, 2016).…”
Section: Introductionunclassified